The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s00401-020-02254-3
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes induce endolysosomal permeabilization as a gateway by which exosomal tau seeds escape into the cytosol

Abstract: The microtubule-associated protein tau has a critical role in Alzheimer’s disease and other tauopathies. A proposed pathomechanism in the progression of tauopathies is the trans-synaptic spreading of tau seeds, with a role for exosomes which are secretory nanovesicles generated by late endosomes. Our previous work demonstrated that brain-derived exosomes isolated from tau transgenic rTg4510 mice encapsulate tau seeds with the ability to induce tau aggregation in recipient cells. We had also shown that exosomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 84 publications
(197 reference statements)
2
87
0
Order By: Relevance
“…Such a redundancy might explain why e.g. neuronal exosomes are internalized by HEK293T cells and vice versa [10,11,16]. Interestingly and although not completely understood, similar to vesicle-free tau seeds, HSPGs also regulate the internalization of exosomes [68,69] (Fig 3B).…”
Section: Accepted Articlementioning
confidence: 96%
See 2 more Smart Citations
“…Such a redundancy might explain why e.g. neuronal exosomes are internalized by HEK293T cells and vice versa [10,11,16]. Interestingly and although not completely understood, similar to vesicle-free tau seeds, HSPGs also regulate the internalization of exosomes [68,69] (Fig 3B).…”
Section: Accepted Articlementioning
confidence: 96%
“…Of note, tau can form proteopathic seeds that propagate transsynaptically and actively corrupt the proper folding of soluble tau in recipient neurons [7][8][9][10][11][12] (Fig 1B). Neuron-to-neuron propagation of tau seeds involves secretion by donor cells and the subsequent internalization by recipient cells, mostly via endocytosis [11,[13][14][15][16]. However, because seeded tau aggregation occurs in the cytosol, endocytosed tau seeds need to escape from the endosomal entrapment in order to access the cytosol and corrupt the proper folding of physiological endogenous tau.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our data we hypothesize that by reducing the transport of tau seeds into lysosomes via PIKfyve inhibition, tau seeding can be halted. In line with this idea it has been recently shown that exosomes containing Tau seeds require transport into the lysosome as well as lysosomal rupture to promote Tau aggregation ( 64 ). Whereas tau-seeds-induced rupture of lysosomes has not been shown yet, other protein oligomers such as α-synuclein fibrils are known to induce rupture of the lysosomal compartment and induce seeding ( 65 ).…”
Section: Discussionmentioning
confidence: 86%
“…However, tau seeding in similar models as ours identifies acidified compartments as a necessary component for tau seeds to enter cells and induce pathology. Disruption of these acidified compartments protected against induced tau aggregation (Polanco et al, 2021).…”
Section: The Implication Of the Endo-lysosomal Systemmentioning
confidence: 99%